2004
DOI: 10.1021/jp040185m
|View full text |Cite
|
Sign up to set email alerts
|

Dimethyl Methylphosphonate Decomposition on Titania-Supported Ni Clusters and Films:  A Comparison of Chemical Activity on Different Ni Surfaces

Abstract: The thermal decomposition of dimethyl methylphosphonate (DMMP) has been studied in ultrahigh vacuum by temperature programmed desorption (TPD) and X-ray photoelectron spectroscopy (XPS) on Ni clusters and films deposited on TiO 2 (110). The four different Ni surfaces under investigation consisted of small Ni clusters (5.0 ( 0.8 nm diameter, 0.9 ( 0.2 nm height) deposited at room temperature and quickly heated to 550 K, large Ni clusters (8.8 ( 1.4 nm diameter, 2.3 ( 0.5 nm height) prepared by annealing to 850 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
127
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(137 citation statements)
references
References 102 publications
10
127
0
Order By: Relevance
“…surface as PO x ; this species begins to form at 323 K and is often seen in studies of DMMP decomposition on metal oxides [18,20,21]. The lack of a resolvable corresponding O 1s component is reasonable considering the small amount of PO x compared to the bulk oxygen.…”
Section: Disclosure Statementmentioning
confidence: 83%
See 1 more Smart Citation
“…surface as PO x ; this species begins to form at 323 K and is often seen in studies of DMMP decomposition on metal oxides [18,20,21]. The lack of a resolvable corresponding O 1s component is reasonable considering the small amount of PO x compared to the bulk oxygen.…”
Section: Disclosure Statementmentioning
confidence: 83%
“…Several DMMP fragments and likely products were monitored, and the results are plotted in Figure 4. The parent ion (124 amu) and another characteristic fragment (79 amu, either PO 3 + or PO 2 CH 4 + ) [18,19] of DMMP show that desorption begins just below 250 K and has a maximum around room temperature, suggesting that DMMP does not strongly adsorb to MoO 3 . These mass spectrometry signals reach baseline levels again at around 450 K. Signals from methyl (15 amu) and methoxy (31 amu), follow the same trend as the parent ion, suggesting no decomposition.…”
Section: High Dmmp Coverage -Heating In 10 Mtorr Dmmpmentioning
confidence: 99%
“…Experiments were conducted on a rutile TiO 2 (110) crystal (1 cm 9 1 cm 9 0.1 cm, Princeton Scientific Corp.) in two ultrahigh vacuum (UHV) chambers, which have been previously described in detail [10,23,29,30,[32][33][34][35]. LEIS and STM experiments were carried out in the first chamber, which has a base pressure of B5 9 10 -11 Torr, and is equipped with a fine focus ion gun (Omicron, ISE100) and hemispherical analyzer (EA125) for LEIS experiments, as well as a variable-temperature STM (Omicron, [10,23,30,32].…”
Section: Methodsmentioning
confidence: 99%
“…During this treatment, the crystal becomes an n-type semiconductor through the loss of oxygen from the crystal. Furthermore, titania is a support that is known to participate in catalytic reactions by providing a source of oxygen for reactions on the metal particles [10,[23][24][25]. Because metals like Pt [26][27][28][29][30] and Ni [23,25] interact strongly with titania while Au [31] does not, it may be possible to tune the extent of cluster-support interactions by changing the bimetallic compositions.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, compounds containing phosphorus and sulfur atoms are typical side-products that coordinate and bind irreversibly to the catalytically active sites of the nanoparticles, causing a gradual deactivation of the metal catalyst. Chen et al reported that small Ni nanoparticles (with main diameters of 5.0 nm) supported on TiO 2 show higher effi ciency than larger particles (8.8 nm) or annealed Ni fi lms in the decomposition of dimethylmethylphosphonate, DMMP (a widely used simulant for organophosphorus nerve agents) into CO and H 2 at room temperature [ 20 ]. However, the reaction left high amounts of carbon and phosphorus adsorbed on the metal catalyst surface.…”
Section: Nanosized Metal Particles For Decontamination Of Cwamentioning
confidence: 99%